Post-apocalyptic Dystopian Fiction: A Comparative Study Of Messianic Figures In Cormac Mccarthy’s The Road And Ahmad Sadaawi’s Frankenstein In Baghdad - Abedalqader, Rahma Mohammad Ahmad (2023)
Recently, criticism of the messianic idea has begun to take another diverse approach within literary and philosophical cultural theory. Apparently, the concept is perceived as a return to or of religion due to the fact that religion currently influences critical thinking. However, there is a shift to a messianic philosophical paradigm that becomes a way of understanding the contemporary situation, even in religious societies. This thesis investigates post-apocalyptic dystopian narratives that address the identification of a unique world messiah for humanity. Throughout history, the concept of a messiah who will bring peace and harmony to the world has been present in a variety of religions and cultures, albeit under different names and with varying interpretations. The concept of the Messiah is fundamental to the three monotheistic religions. In Judaism, he is known as the Messiah, in Christianity as Jesus, and in Islam as Isa Ibn Maryam (peace be upon him). The purpose of this thesis is to explore how the messiah figure is portrayed in contemporary novels from different philosophical messianic views and the post-apocalyptic theory. To achieve this basic objective, a comparative cultural approach is followed to analyze Cormac McCarthy’s The Road and Ahmad Sadaawi’s Frankenstein in Baghdad, employing Walter Benjamin’s historical materialism theory and Jacques Derrida’s poststructuralism philosophical views on indeterminate messianic figures and messianic structures.